2020
DOI: 10.1371/journal.pone.0232178
|View full text |Cite
|
Sign up to set email alerts
|

Physicians’ satisfaction with clinical laboratory services at public hospitals in Ethiopia: A national survey

Abstract: IntroductionPhysician is a central figure in the client list of clinical laboratory. Monitoring physicians' satisfaction with laboratory service is an important indicator of the quality management system and required by international laboratory standards. However, there is no national data on physician satisfaction with laboratory services in Ethiopia. Therefore, the aim of this national survey was to assess satisfaction level of physicians with laboratory services at public hospitals in Ethiopia. MethodsInsti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
18
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(35 citation statements)
references
References 16 publications
9
18
2
1
Order By: Relevance
“…As physicians are the primary clients of laboratories, their perceptions of the services delivered are crucial for quality service improvement of clinical laboratories. A satisfaction survey is one of the many ways where they can express their concerns about the services they have received and their opinions on what needs to be improved (Hailu et al, 2020). To assess this, the researchers utilized a questionnaire focused on five (5) laboratory service qualities: laboratory accessibility, report format, provision of services, TAT, and LIS.…”
Section: Discussionmentioning
confidence: 99%
“…As physicians are the primary clients of laboratories, their perceptions of the services delivered are crucial for quality service improvement of clinical laboratories. A satisfaction survey is one of the many ways where they can express their concerns about the services they have received and their opinions on what needs to be improved (Hailu et al, 2020). To assess this, the researchers utilized a questionnaire focused on five (5) laboratory service qualities: laboratory accessibility, report format, provision of services, TAT, and LIS.…”
Section: Discussionmentioning
confidence: 99%
“…Many aspects of laboratory services could be investigated from the clinician's perspective, such as the availability of ordered tests, courier services, availability of a helpful user guidebook, courtesy and respect, laboratory report format, turnaround time (TAT) of results, noti cation of critical results, and reliability of results [5,6]. Previous studies in Ethiopia have shown that physicians were most dissatis ed with the provision of timely results, advisory services and noti cation of panic values [14][15][16][17], including the behavioural manners of providers [14,18]. However, many argue the validity of user satisfaction as a measure of quality, particularly technical aspects, as users could be more sensitive to behavioural aspects [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…However, many argue the validity of user satisfaction as a measure of quality, particularly technical aspects, as users could be more sensitive to behavioural aspects [18,19]. Previous studies have rarely explored clinicians' satisfaction in relation to objective measures of laboratory practice [11,14,20,21]. Assessment of quality from multiple perspectives could provide a better basis to inform managers on opportunities for balanced and thus sustainable improvement [5,6,20].…”
Section: Introductionmentioning
confidence: 99%
“…A trend of low utilization of laboratory results in patient management has been observed as one of the major factors negatively impacting outcomes for most patients accessing health care services in resource-constrained countries of Sub-Saharan Africa [11,12]. Coupled with the challenges of high disease burden, scarce funding, inadequate health personnel, poor health linkages, and inadequate infrastructure, the practice has the potential to negatively affect the provision of quality health services [13]. We, therefore, undertook a cross-sectional descriptive study of the utilisation of laboratory services by clinicians at NTH and ADCH, two large tertiary referral hospitals in Ndola, Zambia.…”
Section: Introductionmentioning
confidence: 99%